Temporary and part-time employment in the European labor market: factors, trends, features - Pritvorova, T.P.; Simonov, S.G.; Atabayeva, A.K. (BUKETOV BUSINESS REVIEW, 2020)
Object: The object of this article is to investigate factors of temporary and part-time employment emergence in Europe to determine country characteristics and trends in their development in the post-industrial economy conditions. Methods: For the purpose of the research we have used methods of statistical grouping, analysis of dynamics, structure and variation. Statistical analysis of the variation in temporary and part-time employment in European countries is based on the coefficient of variation. We have also used data from Eurostat and the European Social Survey (ESS). Results: We have identified features and both objective and subjective factors contributing to the emergence of non-standard employment forms. We have evaluated homogeneity of the population of European countries on studied non-standard employment types: both temporary and incomplete. Based on the results obtained, the prevalence of temporary and part-time employment in Europe was determined. Based on the rating of countries by the share of non-standard types of employment in the total employment of the population, we have identified leaders and outsiders of the said rating. Conclusions: Statistical analysis has shown growth in both temporary and part-time employment; this reflects one of the trends in the evolution of labor markets in European countries. High coefficient of variation values indicate heterogeneity of European countries in the share of temporary and part-time employment. Indeed, a number of countries enjoy a significant increase and a large coverage scale. And yet there are countries where the applicability of fixed-term and incomplete contracts is quite low, and even if it sees an increase, it is a very slight one. The main reasons for heterogeneity depend on the current economic situation and the level of production development in a particular country. They also lie in differences in the applicable legal acts and measures to protect the employee rights.